Bankruptcy Indicator Frameworks Used In Cross-Country Reviews (Indonesia – Russia Bankruptcy Law) - Hapsari, Recca Ayu Hapsari; Tata Wijayanta; Irna Nurhayati; Stanislav Vladimirov Mladenov (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The differences and similarities in the legal frameworks of Cross-country will shed light on the effectiveness of their respective bankruptcy systems. This research employs a comparative analysis of bankruptcy laws in Indonesia and Russia, with a focus on determining debtor bankruptcy indicators. The methodology comprises qualitative research using normative and empirical juridical approaches to analyze bankruptcy laws in Indonesia and Russia, focusing on determining debtor bankruptcy indicators. Indonesian law focuses on debtors' ability to pay using default lawsuits. In contrast, Russian law traditionally uses the impossibility of payment as a benchmark for insolvency and focuses on meeting creditors' claims. Key indicators of debtor bankruptcy in Indonesia include the inability to fully satisfy creditors' claims and meet mandatory payments. This emphasis on financial obligations plays a critical role in determining insolvency in Indonesian bankruptcy law.